Identifying nineteenth century Trans-Pacific production and trade: A geochemical and stylistic study of Chinese opium pipe bowls from southern New Zealand. (June 2020) - Wu, Peihua; Walter, Richard; Gaffney, Dylan; Gong, Yuxuan; Palin, Mike; Reid, Malcolm
Highlights: Analysis of 19 th century Chinese opium pipe bowls shows many workshops used a single clay source. Opium bowl workshops linked into 19 th century Trans-Pacific trade networks. Opium pipe bowls have regionally specific attributes, plus individual workshop markings. Abstract: This paper reports on aspects of the production and trade of nineteenth century Chinese opium pipe bowls based on an examination of an assemblage from a Chinese goldfields settlement in New Zealand. Using energy dispersive X-ray fluorescence (EDXRF) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) we characterised the clay sources used for pipe production. Comparing those results with a stylistic analysis of the pipe bowls we developed a model for the production of opium pipe bowls and their distribution to nineteenth century Chinese diaspora communities. This is the first study to investigate Chinese opium pipe bowls using a combination of geochemical and stylistic analysis and is a novel application of archaeological science methodologies in Overseas Chinese Archaeology. The work reveals information about a group of potters and their production structures in Southern China and their trading connections in the Trans-Pacific region that had previously been historically and archaeologically opaque.